Building local capacities for women's empowerment - Senkhamty, Phouvanh (Technical Centre for Agricultural and Rural Cooperation, 2018)
The Gender Development Association (GDA) is a Lao non-profit organisation working to promote gender equality through the rule of law and good governance. It has been involved in protecting women and girls from gender-based violence and ensuring that civil society organisations and government agencies, at national and provincial levels, had access to relevant judicial procedures. Starting in 2015, it collected and analysed data on gender-based violence and traditional practices in the ethnic minority areas. As a result of this project, there was an increase in women’s access to information, their decision-making ability showed improvement, and their social security was boosted through livelihood strategies that facilitated their access to resources and employment.